2016
DOI: 10.1007/s10103-016-1961-4
|View full text |Cite
|
Sign up to set email alerts
|

Bond strengths of brackets bonded to enamel surfaces conditioned with femtosecond and Er:YAG laser systems

Abstract: The aim of this study was to compare femtosecond and Er:YAG laser systems with regard to enamel demineralization and bracket bond strength. Human-extracted premolars were randomized to three groups (n = 17) depending on the conditioning treatment used for the buccal surfaces: 37 % orthophosphoric acid, Er:YAG laser etching (MSP mode 120 mJ, 10 Hz, 1.2 W), and femtosecond laser etching (0.4 W, 800 nm, 90 fs/pulse, 1 kHz). Metal brackets were bonded with Transbond XT to the conditioned surfaces and light cured f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…26,27 In addition, Er:YAG laser etching was found to be painless and does not involve either vibration or heat, and the easy maneuvering of the laser apparatus is encouraging to use routinely in similar dental tasks (Usumez et al 2002), (Aglarci et al 2016). 9,13 In the present study, a higher sheer bond strength mean value was recorded in acid etching group (14.71) versus (9.11) for laser group (table 1, Fig.1). These values though seems less for laser group, still however efficient for orthodontic brackets optimal bond strength values lying between 6-8MPa.…”
Section: Discusionsupporting
confidence: 48%
See 1 more Smart Citation
“…26,27 In addition, Er:YAG laser etching was found to be painless and does not involve either vibration or heat, and the easy maneuvering of the laser apparatus is encouraging to use routinely in similar dental tasks (Usumez et al 2002), (Aglarci et al 2016). 9,13 In the present study, a higher sheer bond strength mean value was recorded in acid etching group (14.71) versus (9.11) for laser group (table 1, Fig.1). These values though seems less for laser group, still however efficient for orthodontic brackets optimal bond strength values lying between 6-8MPa.…”
Section: Discusionsupporting
confidence: 48%
“…When addressing laser etching of enamel, many authors suggested that the laser etching is capable of creating remineralization micro spaces that traps free ions and produces a surface that is more acid resistant and less susceptible to caries, as a result, it did not need water spraying or air drying saving precious chair time (sawan et al 2015), (Aglarci et al 2016). 12,13 On the other hand, where phosphoric acid etching has proven to be a reliable method of bonding resins to enamel, a potential disadvantage of enamel acid etching is demineralization of the most superficial layer, a matter of concern for every orthodontic practitioner. As a result of demineralization, the enamel surface is more susceptible to acid attack and caries (Nalçaci et al 2017).…”
Section: Discusionmentioning
confidence: 99%
“…ARI scores are used to evaluate residual adhesive conditions on enamel surfaces after laser treatment. It is found that the rate of teeth with ARI score ≤2 in Er:YAG laser etching group was obviously higher than phosphoric acid etching group [1,15,18,41] of (OR = 10.21, 95% CI range: 2.76–37.85, P < .05, 96.77% vs 69.35%), showed that Er:YAG laser was better than acid etching for cleaning teeth after debonding. Similarly, the rate of teeth with ARI score ≤2 in Er,Cr:YSSG laser was also higher than in the acid group on enamel etching (OR = 3.70, 95% CI range: 1.15–11.88, P < .05, 87.5% vs 67.5%) based on 3 studies, [42–44] indicated that less adhesive left on the enamel surface.…”
Section: Resultsmentioning
confidence: 99%
“…[ 14 – 17 ] However, using acid etching technique, the enamel surface becomes prone to acid attack if it is not completely filled with adhesive. [ 18 , 19 ] Besides, acid etching technique increases the caries susceptibility of the enamel, increases enamel demineralization [ 1 , 20 , 21 ] and results in dissolution of the enamel subsurface. [ 22 , 23 ]…”
Section: Introductionmentioning
confidence: 99%
“…This naturally prevents demineralization from happening in surfaces larger than the bracket area itself. 37 …”
Section: Hilt Indications In Orthodonticsmentioning
confidence: 99%